Kajian Terhadap Pertimbangan Hakim Dalam Memutus Perkara Tindak Pidana Korupsi Saluran Ultra Tegangan Ekstra Tinggi (Sutet) Di Bawah Ancaman Minimum Khusus Studi Kasus di Pengadilan Negeri Wates Kulon Progo - Sutanto Sutanto; Yanto Yanto; Sigit Setyadi (Universitas Janabadra, 2019)
The purpose of this study was to find out and assess the basis of consideration of Wates District Court Judges in deciding cases of Ultra Extra High Voltage Channel SUTET corruption under a special minimum threat and the legal consequences arising from the existence of a mild criminal verdict in the corruption case of the Ultra Extra High Voltage Channel SUTET.This research is empirical legal researchnamely research conducted by conducting field research to obtain primary data as its main resource and secondary data as a supplement. Data that has been collected from the results of research, both library research and field research, will be analyzed qualitatively. The results of this study are: 1 In Article 2 paragraph 1 of Law Number 31 Year 1999 as amended and supplemented by Law Number 20 of 2001, it has been explicitly stipulated regarding the minimum criminal sanctions that must be imposed on the perpetrators non-imprisonment, namely 4 years in prison and a fine of at least Rp. 200,000,000. Although in Article 2 paragraph 1 of Law Number 31 of 1999 as amended and supplemented by Law Number 20 of 2001 which explicitly has determined the minimum criminal sanctions that must be imposed on the perpetrators of the crime, the Judge have a consideration that in order to be able to create a decision that can reflect a judge's sense of justice in deciding each case, it should consider aspects of legal certainty, namely implementing legal justice must also consider moral justice and social conditionsofthe community social justice and 2 In accordance with the aim of punishmentthat gives a sense of deterrent to the convict, convictions solely as a reward of an unlawful act with an emphasis on policing the community, criminal special minimum impact on the lives of the accused while in custody and after the defendant was released from prison and return to the community. Here it can be said impact conviction against the accused of corruption are disconnected special minimum, despite the judge's decision only ruled on special minimum, but the impact of acts of corruption defendant heavier than the result of a criminal act of corruption, because of concerns about the life of the accused later in the general public, among othersloss ofhonor, impoverishment oftheaccused,administrativesanctions he received because of the corruption of corruption itself.